Engineering microscopic delivery systems: a review of dissolving microneedle design, fabrication, and function - Roshan Dave; Swapnali Shinde; Nisha Kalayil; Aarati Budar (Micro and Nano Systems Letters, 2024)
Abstract Dissolving microneedles (DMNs) represent an innovative advancement in drug delivery and skincare technologies, offering significant advantages compared to traditional needles. This paper presents an overview of the historical evolution of microneedles and the rise of dissolving types, exploring their definition, concept, and diverse clinical applications such as vaccinations, drug delivery, and skincare treatments. Design and manufacturing considerations cover the materials employed, fabrication techniques, and methods for characterizing DMNs, focusing on aspects like mechanical strength, dissolution rate, and delivery efficiency. The mechanism of action section examines skin penetration mechanics, the process of microneedle dissolution, controlled release of active compounds, and considerations of biocompatibility and safety. Recent developments in DMNs encompass technological advancements, improved delivery systems, and updates on clinical trials and studies. Challenges and opportunities in scaling up production, overcoming market adoption barriers, and future research directions are discussed, aiming to address unmet medical needs and expand applications. In summary, DMNs have the potential to transform drug delivery and skincare treatments, with ongoing advancements aimed at tackling current challenges and unlocking new opportunities for enhanced healthcare outcomes. Graphical Abstract